Exploring the Effect of Ethylenediamine Concentration on the Optical Properties of Carbon Dots Synthesized from Candlenut Shell Biomass - Marpongahtun Marpongahtun; Tjut Siti Safhura; Amir Hamzah Siregar (Talenta Publisher, 2025)
Carbon dots are fluorescent nanomaterials with a size below 10 nm, known for their good optical properties, including fluorescence emission and biocompatibility which are very suitable for various applications, such as bioimaging, sensors and optoelectronics. This research aims to synthesize CDs and NCDs from candlenut shells as a biomass source using the hydrothermal method at 230°C for 6 hours with the addition of ethylenediamine (EDA) as a nitrogen dopant at concentrations of 4%, 8% and 12% (v/v). The study also evaluates the effect of varying EDA concentrations on the optical properties of CDs and NCDs. Based on the results, under 365 nm UV irradiation, all samples showed bluish green fluorescence. The results of UV-Vis analysis showed an absorption peak at a wavelength of 271 nm for CDs and additional absorption peaks at 274 nm and 324 nm for NCDs, corresponding to the π–π* and n–π* transitions, respectively. Increasing EDA concentration is associated with a gradual decrease in the absorption intensity of CDs and NCDs. The photoluminescence results showed the CDs emission peak at 494 nm with a quantum yield (QY) of 18% and the strongest fluorescence at 498 nm for NCDs 8% with the highest QY of 27%. The results of FTIR analysis showed -OH, C=O and C=N functional groups in all samples and additional -NH functional groups in the NCDs, indicating successful nitrogen incorporation.